Evaluación de parámetros tecnológicos de conserva elaborada a partir de Carachama (Pseudorinelepis genibarbis) en salsa de tomate (Solanum lycopersicum), sacha culantro (Eryngium foetidum L) y ají charapita (Capsicum frutescens) Ucayali-Perú - Ahuanari Usquiano, Gleider Benito (2020)
The main objective of this study was to carry out an evaluation of the production parameters for the manufacture of a canned carachama (Pseudorinelepis genibarbis) taking as the governing liquid the combination of tomato sauce (Solanum lycopersicum), sacha coriander (Eryngium foetidum l) and ají charapita (Capsicum frutescens), in tuna-type cans, considering an experiment with a 3 x 3 factorial arrangement for the purpose. The application of this design allowed to know the influence of various processing parameters on the characteristics of the preserve, specifically in the drained weight, vacuum pressure, liquid of government and sensory characteristics which are established by the Peruvian norms for containers type tuna. After applying the scale tests, analysis of results and developing the statistical analysis ANOVA, it was deduced that the best treatment was in the parameters proposed in treatment 6, whose considerations were for temperature 110 ° C, time 36 min, and pressure 4 psi. In addition, the results of the sensory analysis showed that there are no significant differences between the treatments, which is why it was concluded that treatment six is the most suitable for the processing of canned carachama fish in tuna-type containers.